Analysis of Students’ Mathematical Literacy Skills on Space and Shape Content - Nurwijayanti, Karina; Lestari, Tri Kurniah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study employs a qualitative descriptive design with a case study approach. This study aims to describe students’ mathematical literacy abilities in the Space and Shape content of PISA. The Programme for International Student Assessment (PISA) analytical framework posits that the evaluation of mathematical literacy necessitates an integrated approach involving four primary dimensions: mathematical content, processes, contexts, and competencies. With respect to mathematical content, the framework delineates four distinct categories: Change and Relationships, Space and Shape, Quantity, and Uncertainty and Data. Space and Shape literacy is essential, as it encompasses the ability to understand and interpret forms, space, and real-world situations through geometric representations. This literacy demands the application of geometric concepts, spatial visualization, and the capacities for reasoning, modeling, and reflection in problem-solving. The findings indicate that students’ mathematical literacy skills vary across distinct ability levels. High-ability students successfully fulfill the formulate and employ aspects. Conversely, moderate-ability students encounter difficulties with geometric representation and complex problem-solving, while low-ability students struggle across all stages of the mathematical literacy process. Notably, the interpret aspect is the most frequently unfulfilled component across all student categories. These outcomes demonstrate that the formulate, employ, and interpret processes are interrelated, suggesting that deficiencies in the initial stages impede success in subsequent phases. The implications of this research suggest the necessity of problem-based and contextual learning supported by visual representations, mathematical discussions, reflection, and scaffolding strategies to develop students’ formulate, employ, and interpret competencies in solving real-world problems.